2022
DOI: 10.3390/vaccines10091453
|View full text |Cite
|
Sign up to set email alerts
|

Parental Willingness and Associated Factors of Pediatric Vaccination in the Era of COVID-19 Pandemic: A Systematic Review and Meta-Analysis

Abstract: A significant decline in pediatric vaccination uptake due to the COVID-19 pandemic has been documented. Little is known about the parental willingness and associated factors of pediatric vaccination during the COVID-19 pandemic. An extensive literature search in the databases of PubMed, Scopus, Web of Science, and EBSCOhost were conducted. A total of 20 eligible studies published from 2020–2022 were included for systematic summary by a thematic analysis, among which 12 studies were included in a meta-analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…Although declining overall vaccination rates have been reported in some studies, a recent meta-analysis of 27 pandemic-era studies (January 2019-December 2021) found there was increased intention to vaccinate across age, sex, and occupation [31,32]. This effect was also seen in parental willingness to consent to vaccination [35]. Our study indicates similarly held views among adults in Tennessee, with participants noting that seeing the effects of COVID-19 in the population at large and within their own social networks made them more cognizant of the dangers of infectious diseases and potential benefits of immunization.…”
Section: Discussionmentioning
confidence: 97%
“…Although declining overall vaccination rates have been reported in some studies, a recent meta-analysis of 27 pandemic-era studies (January 2019-December 2021) found there was increased intention to vaccinate across age, sex, and occupation [31,32]. This effect was also seen in parental willingness to consent to vaccination [35]. Our study indicates similarly held views among adults in Tennessee, with participants noting that seeing the effects of COVID-19 in the population at large and within their own social networks made them more cognizant of the dangers of infectious diseases and potential benefits of immunization.…”
Section: Discussionmentioning
confidence: 97%
“…In the case of a new vaccine against RSV, therefore, it is necessary to plan educational interventions aimed at HCWs, especially pediatricians, to enable them to learn the necessary information to be transferred to parents. Examples of educational strategies could be face-to-face and online courses to increase vaccine knowledge or offering interactive approaches with roleplay sections to support comfort level and perceived effectiveness when counseling vaccine-hesitant parents [38].…”
Section: Discussionmentioning
confidence: 99%
“…This information is also important to oral healthcare and public health professionals, as recent evidence has demonstrated that vaccine hesitancy (particularly related to HPV among pediatric patients) has been increasing in recent years despite strong evidence for the efficacy and safety of both the quadrivalent and nine-valent HPV vaccines [ 38 , 39 , 40 ]. In fact, other recent evidence has also documented the increase in vaccine hesitancy and skepticism about vaccine safety and efficacy over recent years among children, adolescents, and their parents [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the paucity of information regarding HPV52 and HPV58 prevalence among any patient population, this study provides significant evidence that these high-risk strains are present among both pediatric and adult populations [ 32 , 33 ]. In addition, these data also demonstrated that the majority of samples with HPV were derived from patients within the recommended HPV vaccination range, providing significant information for health professionals and public health advocates on the urgent need to disseminate current knowledge about the benefits of the nine-valent HPV vaccine and the potential risks of avoidance for this low-cost and effective prevention method [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%